Negative electrode for electricity storage device, and electricity storage device
By using small molecular weight cellulose derivatives and high -circular adhesive particles in the negative active material layer of the storage element, the power storage element is solved The problem realizes higher Kuron efficiency and lower resistance, and improves charging acceptance.
Patent Information
- Application Number
- CN202380046970.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-05-24
- Publication Date
- 2025-01-28
AI Technical Summary
After repeated charging and discharging of high current density, the existing power storage components have low efficiency and high resistance, and charge transport ions such as metal lithium precipitate on the surface of the negative electrode, affecting charging acceptability.
Using negative active substances containing negative active substances, cellulose derivatives and adhesive particles, the peak molecular weight of cellulose derivatives is 2,800,000, and the average circularity of the adhesive particles is more than 0.90 to improve the efficiency of Kuron And reduce resistance.
The Kuron efficiency of the storage component is significantly improved, the resistance is reduced, and the phenomenon of metal lithium on the negative surface of the metal lithium is inhibited, and the charging acceptance is improved.
Smart Images

Figure CN119384727A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for an energy storage element and an energy storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. due to their high energy density. In addition, as storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors, and storage elements using electrolytes other than non-aqueous electrolytes are also widely used.
[0003] The electrode provided in the storage element generally has a structure in which an active material layer containing an active material is formed on the surface of a conductive substrate such as a metal foil. The negative electrode active material layer is formed by, for example, applying a mixture paste containing a negative electrode active material such as graphite, a binder such as styrene butadiene rubber (SBR), a thickener such as carboxymethyl cellulose (CMC), and a dispersion medium such as water and drying it (see Patent Document 1). Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2005-11808 Summary of the invention Problems to be solved by the invention
[0005] The storage element is required to have high coulombic efficiency. Coulombic efficiency is the ratio of discharge capacity to charge capacity. In addition, the inventors found that when the coulombic efficiency of the storage element after repeated charge and discharge at a high current density is high, the precipitation of metals obtained by reducing charge transport ions such as metallic lithium on the negative electrode surface is suppressed, and there is a tendency for high charge acceptance. Furthermore, from the perspective of input and output performance, it is preferred that the resistance of the storage element is low.
[0006] An object of the present invention is to provide a negative electrode for an electric storage element capable of improving the coulombic efficiency of an electric storage element and reducing the resistance, and an electric storage element including such a negative electrode. Methods for solving problems
[0007] A negative electrode for an electric storage device according to one aspect of the present invention comprises a negative electrode active material layer containing a negative electrode active material, a cellulose derivative and binder particles, wherein the peak top molecular weight of the cellulose derivative is 2,800,000 or less, and the average circularity of the binder particles is 0.90 or more.
[0008] An electric storage device according to another aspect of the present invention includes the negative electrode for an electric storage device according to one aspect of the present invention. Effects of the Invention According to one aspect of the present invention, it is possible to provide a negative electrode for an electric storage element capable of improving the coulombic efficiency of an electric storage element and reducing the resistance thereof, and an electric storage element including such a negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a perspective view showing an embodiment of an electric storage element. Figure 2 This is a schematic diagram showing one embodiment of a power storage device constituted by a collection of a plurality of power storage elements. DETAILED DESCRIPTION
[0011] First, the outline of the negative electrode for an electric storage device and the electric storage device disclosed in this specification will be described.
[0012] [1] A negative electrode for an electric storage device according to one aspect of the present invention comprises a negative electrode active material layer containing a negative electrode active material, a cellulose derivative, and binder particles, wherein the peak top molecular weight of the cellulose derivative is 2,800,000 or less, and the average circularity of the binder particles is 0.90 or more.
[0013] The negative electrode for the storage element described in [1] can improve the coulombic efficiency of the storage element and reduce the resistance. The reason for this effect is not certain, but the following reasons are speculated. Cellulose derivatives with a small molecular weight have less steric hindrance than cellulose derivatives with a large molecular weight. Therefore, in the negative electrode active material layer using a cellulose derivative with a small molecular weight, charge transport ions such as lithium ions are easy to move, and the coulombic efficiency is improved. On the other hand, when a cellulose derivative with a small molecular weight is used, due to the small steric hindrance, during the period of applying the negative electrode mixture paste and drying it, the binder particles are easy to move to the surface of the negative electrode mixture paste together with the dispersion medium, and there is a tendency for the resistance to increase due to the aggregation of the binder particles. It is believed that the larger the area of the surface of the negative electrode active material coated by the binder particles, the higher the resistance of the storage element. Therefore, it is believed that when the average circularity of the binder particles is high, even when the binder particles are aggregated, the area of the surface of the negative electrode active material coated by the binder particles is small, resulting in low resistance. From the above, it is estimated that the negative electrode for an electric storage device described in [1], wherein the peak top molecular weight of the cellulose derivative is 2,800,000 or less and the average circularity of the binder particles is 0.90 or more, can improve the coulombic efficiency of the electric storage device and reduce the resistance.
[0014] In addition, the negative electrode for an electric storage device according to one aspect of the present invention can suppress the deposition of metal on the negative electrode surface resulting from the reduction of charge transport ions such as metallic lithium after repeated charge and discharge, and can also improve the charge acceptance of the electric storage device.
[0015] The peak molecular weight of the cellulose derivative is set to the value obtained by the gel permeation chromatography (GPC) measurement in the following steps. 5 mg of the cellulose derivative to be measured is dissolved in 5 mL of water to obtain a solution. The solution is filtered with a hydrophilic PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm, and the filtrate is subjected to GPC measurement. The molecular weight corresponding to the peak of the differential molecular weight distribution curve obtained by GPC measurement is the peak molecular weight. The GPC measurement conditions are as follows. [GPC measurement conditions] Column / Temperature: 2 x "OHpak SB-806M HQ", 8.0 mm x 30 cm (Shodex) / 40°C Mobile phase: 0.1 mol / dm 3 NaCl aqueous solution Flow rate: 1.0mL / min. Injection volume: 100 μL Detection: Differential Refractometer (RI) Column calibration: Monodisperse pullulan Molecular weight calibration: relative calibration method (pullulan conversion) Measuring device: Dual pump "KP-22-13" (FLOM), automatic injection device "717plus" (Waters, Japan), differential refractive index detector "RI-101" (Shodex) Analysis software: Empower3 (Waters, Japan)
[0016] Here, the reason for determining the molecular weight of the cellulose derivative by the peak molecular weight is explained. When the filtrate for GPC measurement is prepared by the above method, the insoluble components in the cellulose derivative are sometimes removed during filtration. Typically, components with large molecular weights have low solubility in water and tend to be removed during filtration. Therefore, even for cellulose derivatives with the same actual weight-average molecular weight, the portion of the substance with more components with large molecular weights removed becomes more than that of the substance with fewer components with large molecular weights, so the measured weight-average molecular weight becomes smaller. On the other hand, in the case of the peak molecular weight, even if the component with a molecular weight larger than the peak molecular weight is removed during filtration, the measured peak molecular weight is also the same value, and the influence of filtration on the measured value is small. Therefore, in the present invention, which exerts its effect by the small molecular weight of the cellulose derivative, it is inappropriate to determine the molecular weight of the cellulose derivative by the weight-average molecular weight, but the molecular weight of the cellulose derivative is determined according to the peak molecular weight.
[0017] The "average circularity" of the adhesive particles is the average value of the circularity of any 25 adhesive particles. In the case where the adhesive particles have a carbon-carbon double bond (-CH=CH- bond) and in the case where they have an ethylene unit (-CH2-CH2-), the circularity of each adhesive particle is measured based on an image analysis of a scanning electron microscope (SEM) image of the adhesive particles stained with electrons. In the case where the adhesive particles do not have either a carbon-carbon double bond or an ethylene unit, the circularity is measured based on an image analysis of a scanning electron microscope-energy dispersive X-ray spectrometry (SEM-EDX) image of the adhesive particles based on the elements contained in the adhesive particles. The SEM image of the binder particles was obtained by the following procedure. (1) Preparation of test samples When the binder particles have a carbon-carbon double bond (-CH=CH- bond), osmium tetroxide is used as the negative electrode to be measured, and when it has an ethylene unit (-CH2-CH2-), ruthenium tetroxide is used to implement electronic staining. The cross section of the sample to which electronic staining is implemented is exposed by ion milling to prepare a sample for measurement. It should be noted that the negative electrode to be measured is prepared by the following steps. In the case where the negative electrode before assembling the storage element can be prepared, it is used directly. In the case of preparing from the assembled storage element, first, the storage element is discharged at a constant current of 0.1C to the discharge termination voltage during normal use, and the state after discharge is set. The storage element in the discharged state is disassembled, the negative electrode is taken out, and after being thoroughly cleaned with dimethyl carbonate, it is dried under reduced pressure at room temperature. The operation from the disassembly of the storage element to the preparation of the negative electrode to be measured is carried out in a dry air atmosphere with a dew point below -40°C. “In normal use” means a case where the energy storage element is used under the charge and discharge conditions recommended or specified for the energy storage element. When a device for using the energy storage element is prepared, it means a case where the energy storage element is used using the device. (2) Acquisition of SEM images When obtaining the SEM image, JSM-7001F (manufactured by JEOL Ltd.) was used as a scanning electron microscope. The SEM image is an image of observed reflected electrons. The accelerating voltage was set to 5 kV. The observation magnification was set to a magnification when the number of adhesive particles appearing in a field of view was more than 25 and less than 200. The obtained SEM image was saved as an image file. In addition, the conditions such as the spot diameter, working distance, irradiation current, brightness, and focus were appropriately set in a manner that the outline of the adhesive particles became clear. (3) Image analysis The obtained SEM image is subjected to image analysis, and the area and the perimeter length of any 25 adhesive particles are measured. Image analysis is performed using image analysis software PopImaging6.00. However, other software capable of performing image analysis equivalent to the image analysis software can also be used. The circularity of each adhesive particle is calculated by the following formula, and its average value is used as the "average circularity" of the adhesive particle. Circularity = (4π × area of particle) / (circumference of particle) 2 The SEM-EDX image of the binder particles was obtained by the following procedure. (1) Preparation of test samples A measurement sample was prepared in the same manner as in the step (1) of obtaining the SEM image of the binder particles, except that electron staining was not performed. (2) Acquisition of SEM-EDX images When obtaining the SEM-EDX image, JSM-IT500 (manufactured by JEOL Ltd.) is used as a scanning electron microscope. In the case of adhesive particles that do not have carbon-carbon double bonds and ethylene units such as polytetrafluoroethylene and polyvinylidene fluoride and contain fluorine, the fluorine element is measured as the object. In the case where the measured element is unclear, a qualitative analysis is first performed, for example, in comparison with the analysis results of the negative electrode using styrene butadiene rubber as the adhesive particle, the element with a large amount of detection other than carbon or oxygen is measured as the object. About the accelerating voltage, in order to improve the spatial resolution, it is set as low as possible within the range of the element that can be measured as the object. The observation magnification is set to the magnification when the adhesive particles appearing in a field of view are more than 25 and less than 200. The obtained SEM-EDX image is saved as an image file. In addition, each condition such as spot diameter, working distance, irradiation current, brightness, focusing, etc. is appropriately set in a way that the outline of the adhesive particles becomes clear. (3) Image analysis The image analysis of the obtained SEM-EDX image is performed in the same manner as step (3) of obtaining the SEM image of the binder particles, by measuring the area and circumference of each of 25 arbitrary particles. The circularity of each binder particle is calculated by the following formula, and the average value is taken as the "average circularity" of the binder particles. Circularity = (4π × area of particle) / (circumference of particle) 2
[0018] [2] In the negative electrode for an electric storage device described in [1] above, the negative electrode active material may be a carbon material, and the negative electrode active material layer may contain 90% by mass or more of the negative electrode active material.
[0019] According to the negative electrode for an electric storage element described in the above [2], the coulombic efficiency of the electric storage element can be improved more reliably and the resistance can be reduced.
[0020] [3] In the negative electrode for an electric storage device described in [1] or [2] above, the binder particles may include particles of styrene butadiene rubber.
[0021] According to the negative electrode for an electric storage element described in the above [3], the coulombic efficiency of the electric storage element can be improved more reliably and the resistance can be reduced.
[0022] [4] In the negative electrode for an electric storage device according to any one of [1] to [3] above, the cellulose derivative may include carboxymethyl cellulose.
[0023] According to the negative electrode for an electric storage element described in the above [4], the coulombic efficiency of the electric storage element can be improved more reliably and the resistance can be reduced.
[0024] [5] An electric storage device according to another aspect of the present invention includes the electric storage device negative electrode according to any one of [1] to [4].
[0025] Since the electric storage device described in [5] above includes the electric storage device negative electrode described in any one of [1] to [4] above, the coulombic efficiency is improved and the resistance is reduced.
[0026] Hereinafter, a negative electrode for a storage element, a storage element, a storage device, a method for manufacturing a storage element, and other embodiments of the present invention are described in detail. It should be noted that the names of the constituent components (constituent elements) used in each embodiment are sometimes different from the names of the constituent components (constituent elements) used in the background art.
[0027] <Negative electrode for energy storage element> A negative electrode for an electric storage device (hereinafter also referred to simply as "negative electrode") according to one embodiment of the present invention comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The negative electrode is used in electric storage devices such as secondary batteries.
[0028] The negative electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity measured in accordance with JIS-H-0505 (1975) with a value of 10 -2 Ω·cm is the threshold value for judgment. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbonaceous materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be listed. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be listed.
[0029] The average thickness of the negative electrode substrate is preferably 2 μm or more and 35 μm or less, more preferably 3 μm or more and 30 μm or less, further preferably 4 μm or more and 25 μm or less, and particularly preferably 5 μm or more and 20 μm or less. By setting the average thickness of the negative electrode substrate to the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the storage element can be increased.
[0030] The intermediate layer is a layer disposed between the negative electrode substrate and the negative electrode active material layer. The intermediate layer reduces the contact resistance between the negative electrode substrate and the negative electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.
[0031] The negative electrode active material layer contains a negative electrode active material, a cellulose derivative, and binder particles, and optionally contains a conductive agent, a filler, and other optional components.
[0032] The negative electrode active material can be appropriately selected from known negative electrode active materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 、LiTiO 2、 Titanium-containing oxides such as TiNb2O7; polyphosphate compounds; silicon carbide; carbon materials such as graphite, non-graphite carbon (graphitizable carbon or non-graphitizable carbon), etc. Among these materials, graphite and non-graphite carbon are preferred, and graphite is more preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0033] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge / discharge or in a discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.
[0034] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in a discharged state. 002 ) is a carbon material having a diameter of 0.34 nm or more and 0.42 nm or less. Examples of non-graphite carbon include difficult-graphitization carbon and easy-graphitization carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.
[0035] Here, the "discharge state" of the carbon material as the negative electrode active material refers to a state in which the carbon material as the negative electrode active material is discharged in a manner in which lithium ions that can be stored and released accompanying charge and discharge are fully released. For example, in a half-cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and using metal Li as a counter electrode, it is a state in which the open circuit voltage is 0.7V or more.
[0036] "Non-graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.36 nm or more and 0.42 nm or less.
[0037] "Graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.
[0038] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be set to, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide or a polyphosphate compound, its average particle size can be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can be 1 nm or more and 1 μm or less. By making the average particle size of the negative electrode active material above the above lower limit, the manufacture or handling of the negative electrode active material becomes easy. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. The "average particle size" of the negative electrode active material and the positive electrode active material described later refers to the value of 50% of the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) based on the particle size distribution measured by the laser diffraction scattering method on the diluted solution obtained by diluting the particles with a solvent in accordance with JIS-Z-8825 (2013).
[0039] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a cyclone jet mill, or a sieve can be cited. During pulverization, wet pulverization in which an organic solvent such as water or hexane coexists can also be used. As a classification method, a sieve, a pneumatic classifier, etc. can be used as needed in a dry or wet method.
[0040] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, more preferably 90% by mass or more and 98% by mass or less, and sometimes more preferably 95% by mass or more. By setting the content of the negative electrode active material to the above range, the high energy density and manufacturability of the negative electrode active material layer can be taken into account.
[0041] The cellulose derivative is generally a component that functions as a thickener when forming a negative electrode active material layer by coating of a negative electrode mixture paste or the like.
[0042] Cellulose derivatives are compounds having a structure in which at least a part of the hydrogen atoms of the hydroxyl groups possessed by cellulose are substituted by other groups. Examples of cellulose derivatives include carboxyalkyl cellulose (carboxymethyl cellulose (CMC), carboxyethyl cellulose, carboxypropyl cellulose, etc.), alkyl cellulose (methyl cellulose, ethyl cellulose, etc.), hydroxyalkyl cellulose (hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, etc.), cellulose acetate phthalate, hydroxypropyl methyl cellulose phthalate, acetyl cellulose, etc. Among them, carboxyalkyl cellulose is preferred, and CMC is more preferred. Cellulose derivatives may be used alone or in combination of two or more.
[0043] A part or all of the cellulose derivative may be present in the form of a salt. Examples of the salt form include alkali metal salts (eg, sodium salts) and ammonium salts.
[0044] The upper limit of the peak molecular weight of the cellulose derivative is 2,800,000, preferably 2,700,000, and more preferably 2,600,000. By making the peak molecular weight of the cellulose derivative below the above upper limit, the coulombic efficiency of the storage element can be improved. The lower limit of the peak molecular weight of the cellulose derivative is preferably 100,000, more preferably 200,000, further preferably 500,000, and further preferably 1,000,000, 1,500,000 or 2,000,000. By making the peak molecular weight of the cellulose derivative above the above lower limit, sufficient viscosity can be given to the negative electrode mixture paste when forming the negative electrode active material layer, and the negative electrode active material layer can be efficiently formed. In addition, when the peak molecular weight of the cellulose derivative is above the above lower limit, the aggregation of the binder particles can also be suppressed due to moderate steric hindrance. As a result, a more uniform negative electrode active material layer can be formed, and the adhesion with the negative electrode substrate is improved, and as a result, a storage element with excellent charge-discharge cycle performance can be provided. In addition, by making the peak top molecular weight of the cellulose derivative greater than the above lower limit, the resistance of the storage element can be reduced. The peak top molecular weight of the cellulose derivative can be in the range of greater than any of the above lower limits and less than any of the above upper limits.
[0045] The content of the cellulose derivative in the negative electrode active material layer is not particularly limited, for example, it can be 0.1% by mass or more and 10% by mass or less, preferably 0.2% by mass or more and 5% by mass or less, more preferably 0.3% by mass or more and 4% by mass or less, further preferably 0.4% by mass or more and 3% by mass or less, further preferably 0.5% by mass or more and 2% by mass or less, further preferably 0.8% by mass or more and 1.5% by mass or less. By making the content of the cellulose derivative above the lower limit, the negative electrode mixture paste when forming the negative electrode active material layer can be given sufficient viscosity, and the negative electrode active material layer can be efficiently formed. On the other hand, by making the content of the cellulose derivative below the upper limit, the charge transport ions are more easily moved in the negative electrode active material layer, and the coulombic efficiency is further improved.
[0046] Binder particles are particles of binder. In other words, in the negative electrode active material layer, the binder exists in the form of particles. As binders constituting binder particles, for example, thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc. can be cited. Among them, elastomers are preferred, and SBR is more preferred.
[0047] The lower limit of the average circularity of the binder particles is 0.90, preferably 0.91, and more preferably 0.92. By making the average circularity of the binder particles above the above lower limit, the surface area of the binder particles coated with the negative electrode active material becomes smaller, and the resistance of the storage element can be reduced. On the other hand, the upper limit of the average circularity of the binder particles can be 1.00, or 0.99, 0.97, 0.95 or 0.94. The average circularity of the binder particles can be a range above any of the above lower limits and below any of the above upper limits.
[0048] The average circularity of the binder particles can be controlled, for example, according to the type of binder used, degree of polymerization, glass transition temperature, manufacturing conditions, etc. For example, a binder with a large degree of polymerization, a binder with a high glass transition temperature, etc., tends to have an increased average circularity. The binder can use a commercially available product. For example, various commercially available binders are used to form negative electrode active material layers, respectively, and the average circularity of the binder particles in each negative electrode active material layer is measured, and an binder with an average circularity of 0.90 or more is selected. In addition, when forming the negative electrode active material layer, when the pressing pressure is large, there is a tendency for the binder particles to be crushed and the average circularity to decrease.
[0049] The average particle size of the binder particles is preferably 50 nm or more and 500 nm or less, more preferably 100 nm or more and 400 nm or less, and further preferably 150 nm or more and 300 nm or less. When the average particle size of the binder particles is within the above range, the coulomb efficiency of the storage element can be further improved and the resistance can be further reduced. The average particle size of the binder particles is set to the average value of the equivalent circle diameters of any 25 binder particles in the SEM image when the average circularity is obtained.
[0050] The content of the binder particles in the negative electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 5% by mass or less, further preferably 0.3% by mass or more and 3% by mass or less, and further preferably 0.5% by mass or more and 2% by mass or less. By setting the content of the binder particles to the above range, the negative electrode active material can be stably maintained. In addition, by making the content of the binder particles above the above lower limit, the adhesion between the negative electrode active material and the negative electrode substrate or the negative electrode active material can be improved to ensure manufacturability. On the other hand, by making the content of the binder particles below the above upper limit, the charge transport ions are more easily moved in the negative electrode active material layer, and the coulombic efficiency is further improved. Usually, the content of the binder particles in the negative electrode active material layer is equal to the content of the binder in the negative electrode active material layer.
[0051] The conductive agent is not particularly limited as long as it is a material with conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, etc. Examples of carbonaceous materials include graphite, non-graphite carbon, graphene-based carbon, etc. Examples of non-graphite carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, etc. Examples of carbon black include furnace black, acetylene black, Ketjen black, etc. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, etc. Examples of the shape of the conductive agent include powder, fiber, etc. Examples of the conductive agent include one of these materials alone, or a mixture of two or more. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among them, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.
[0052] When the negative electrode active material layer contains a conductive agent, the content of the conductive agent in the negative electrode active material layer is, for example, 1% by mass or more and 10% by mass or less. The content of the conductive agent in the negative electrode active material layer may be 5% by mass or less, 2% by mass or less, 1% by mass or less, 0.1% by mass or less, or 0% by mass.
[0053] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene; inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; carbonates such as calcium carbonate; poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate; nitrides such as aluminum nitride and silicon nitride; and mineral resources such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0054] When the negative electrode active material layer contains a filler, the content of the filler in the negative electrode active material layer is, for example, 0.1 mass % to 5 mass %. The content of the filler in the negative electrode active material layer may be 1 mass % or less, 0.1 mass % or less, or 0 mass %.
[0055] The negative electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, cellulose derivatives, binder particles, conductive agents, and fillers.
[0056] The density of the negative electrode active material layer is preferably 1.1 g / cm 3 Above and 1.7g / cm 3 Below, more preferably 1.2 g / cm 3 Above and 1.6g / cm 3 Below, more preferably 1.3 g / cm 3 Above and 1.5g / cm 3 Below. By making the density of the negative electrode active material layer above the above lower limit, the energy density of the storage element can be improved. In addition, usually, if the density of the negative electrode active material layer is high, the gaps in the negative electrode active material layer are narrow, and therefore it is easily affected by the steric hindrance of the cellulose derivative. Therefore, in the case where the density of the negative electrode active material layer is above the above lower limit, the effect of the present invention is particularly significantly produced, that is, using a cellulose derivative with a small peak molecular weight to reduce steric hindrance and improve coulombic efficiency. In addition, by making the density of the negative electrode active material layer below the above upper limit, the charge transport ions are more likely to move in the negative electrode active material layer, and the coulombic efficiency is further improved. The density of the negative electrode active material layer can be adjusted according to the pressing strength of the negative electrode active material layer during the negative electrode manufacturing process, etc.
[0057] The density of the negative electrode active material layer (g / cm 3) is a value calculated based on the mass per unit area of the negative electrode active material layer and the average thickness of the negative electrode active material layer. That is, the "density" of the negative electrode active material layer is the apparent density. The average thickness of the negative electrode active material layer refers to the average value of the thickness measured at any 5 locations. It should be noted that, in the case where the negative electrode active material layer is formed on both sides of the negative electrode substrate, it is set to the mass per unit area and the average thickness of the negative electrode active material layer formed on either side of the negative electrode substrate.
[0058] The manufacture of the negative electrode can be carried out, for example, by coating the negative electrode mixture paste on the negative electrode substrate directly or through an intermediate layer and drying it. After drying, pressing and the like can be performed as needed. The negative electrode mixture paste contains various components constituting the negative electrode active material layer, such as a negative electrode active material, a cellulose derivative, and binder particles. The negative electrode mixture paste usually also contains a dispersion medium. As the dispersion medium, it is preferred to use a dispersion medium with low solubility of the binder particles, typically a dispersion medium in which the solubility of the binder particles relative to 100 parts by mass of the dispersion medium at 20°C is less than 1 part by mass.
[0059] <Electrical storage element> The storage element of one embodiment of the present invention comprises an electrode body, an electrolyte and a container for accommodating the electrode body and the electrolyte, wherein the electrode body has a positive electrode, a negative electrode and a separator. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator between them, or a wound type in which a positive electrode and a negative electrode are wound with a separator between them. The electrolyte exists in a state of being impregnated in the positive electrode, the negative electrode and the separator. As an example of a storage element, a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery") using a non-aqueous electrolyte as an electrolyte is described.
[0060] (positive electrode) The positive electrode comprises a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the negative electrode described above.
[0061] The positive electrode substrate has conductivity. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoint of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, net, porous material, etc. can be listed, and from the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.
[0062] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, further preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate to the above range, the strength of the positive electrode substrate can be increased, and the energy density per unit volume of the storage element can be increased.
[0063] The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer contains any components such as a conductive agent, a binder, a thickener, and a filler as needed. Any components such as a conductive agent and a filler can be selected from the materials exemplified for the above-mentioned negative electrode. In addition, the binder can be selected from the materials exemplified as a binder constituting the binder particles contained in the negative electrode active material layer. The thickener can be exemplified by the cellulose derivative contained in the above-mentioned negative electrode active material layer.
[0064] As the positive electrode active material, it can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the positive electrode active material, for example, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be listed. As lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, for example, Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), etc. As lithium transition metal composite oxides having a spinel crystal structure, Li xMn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be listed. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be listed. The atoms or polyanions in these materials can be partially replaced by atoms or anions composed of other elements. The surfaces of these materials can also be coated with other materials. In the positive electrode active material layer, one of these materials can be used alone, or two or more of them can be mixed and used.
[0065] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, not less than 0.1 μm and not more than 20 μm. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or processing of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that, when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is used as the average particle size of the positive electrode active material. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified for the above-mentioned negative electrode, for example.
[0066] The content of the positive electrode active material in the positive electrode active material layer is preferably 50 mass % or more and 99 mass % or less, more preferably 70 mass % or more and 98 mass % or less, further preferably 80 mass % or more and 95 mass % or less. By setting the content of the positive electrode active material to the above range, it is possible to take into account the high energy density and manufacturability of the positive electrode active material layer.
[0067] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % to 10 mass %, more preferably 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the storage element can be increased.
[0068] The content of the binder in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, and more preferably 3% by mass or more and 9% by mass or less. By setting the content of the binder within the above range, the positive electrode active material can be stably retained.
[0069] When the positive electrode active material layer contains a thickener, the content of the thickener in the positive electrode active material layer is, for example, 0.1 mass % or more and 10 mass % or less. The content of the thickener in the positive electrode active material layer can be 5 mass % or less, 2 mass % or less, 1 mass % or less, 0.1 mass % or less or 0 mass %.
[0070] When the positive electrode active material layer contains a filler, the content of the filler in the positive electrode active material layer is, for example, 0.1 mass % or more and 5 mass % or less. The content of the filler in the positive electrode active material layer may be 1 mass % or less, 0.1 mass % or less, or 0 mass %.
[0071] The positive electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0072] The manufacture of the positive electrode can be carried out, for example, by applying a positive electrode mixture paste directly or via an intermediate layer on the positive electrode substrate and drying it. After drying, pressing can be performed as needed. The positive electrode mixture paste contains the positive electrode active material and various components constituting the positive electrode active material layer, such as a conductive agent and a binder as arbitrary components. The positive electrode mixture paste usually also contains a dispersion medium.
[0073] (negative electrode) The negative electrode included in the electric storage element is the above-mentioned negative electrode for an electric storage element according to one embodiment of the present invention.
[0074] (Diaphragm) The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer including heat-resistant particles and a binder formed on one or both sides of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of shutdown function, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material compounded with these resins can be used.
[0075] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be listed. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, etc., or their artificial products, etc. As inorganic compounds, monomers or complexes of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the electric storage element.
[0076] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the “porosity” refers to a value based on volume, and refers to a value measured by a mercury porosimeter.
[0077] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As a polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. When using a polymer gel, it has the effect of suppressing leakage. As a separator, a porous resin film or a nonwoven fabric as described above can be used together with a polymer gel.
[0078] (Non-aqueous electrolyte) The non-aqueous electrolyte can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte can be a non-aqueous electrolyte solution. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0079] As nonaqueous solvent, it can be suitably selected from known nonaqueous solvents. As nonaqueous solvent, cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc. can be enumerated. As nonaqueous solvent, it can be used that the part of hydrogen atom contained in these compounds is replaced by halogen compound.
[0080] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC is preferred.
[0081] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.
[0082] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, and more preferably a cyclic carbonate and a chain carbonate are used in combination. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted to improve the ion conductivity of the non-aqueous electrolyte. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be suppressed to a lower level. In the case of using a cyclic carbonate and a chain carbonate in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is preferably in the range of 5:95 to 50:50, for example.
[0083] The electrolyte salt may be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts. Among them, lithium salts are preferred.
[0084] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), lithium bis(oxalate)difluorophosphate (LiFOP), lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3 can be cited. Among them, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0085] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 Above and 2.5 mol / dm 3 Below, more preferably 0.3 mol / dm 3 Above and 2.0 mol / dm 3 Below, more preferably 0.5 mol / dm 3 Above 1.7 mol / dm 3Below, particularly preferably 0.7 mol / dm 3 Above 1.5 mol / dm 3 By setting the content of the electrolyte salt to the above range, the ion conductivity of the non-aqueous electrolyte can be improved.
[0086] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, Butylbenzene, tert-amylbenzene, diphenyl ether, dibenzofuran and other aromatic compounds; 2-fluorobiphenyl, o-cyclohexylfluorobenzene, p-cyclohexylfluorobenzene and other partial halides of the above aromatic compounds; 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,5-difluoroanisole and other halogenated anisole compounds; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride anhydride, citraconic anhydride, glutaric anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, cyclopentane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiapentane), 4-methyl Sulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, monofluorolithium phosphate, difluorolithium phosphate, etc. These additives may be used alone or in combination of two or more.
[0087] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01 mass % or more and 10 mass % or less relative to the mass of the entire nonaqueous electrolyte, more preferably 0.1 mass % or more and 7 mass % or less, further preferably 0.2 mass % or more and 5 mass % or less, particularly preferably 0.3 mass % or more and 3 mass % or less. By setting the content of the additive to the above range, it is possible to improve the capacity maintenance performance or cycle performance after high temperature storage, and further improve safety.
[0088] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0089] The solid electrolyte can be selected from any material that has lithium, sodium, calcium, or other ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.) Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.
[0090] In the case of lithium ion secondary batteries, examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.
[0091] The shape of the electric storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.
[0092] Figure 1 The figure shows a storage element 1 as an example of a square battery. It should be noted that the figure is a perspective view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator interposed therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.
[0093] <Electrical Storage Device> The storage element of this embodiment can be installed as a storage unit (battery module) composed of a plurality of storage elements in an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) and other automotive power sources, a personal computer, a communication terminal and other electronic equipment power sources or a power storage power source, etc. In this case, it is sufficient to apply the technology of the present invention to at least one storage element included in the storage unit.
[0094] Figure 2 An example of an electric storage device 30 is shown in which an electric storage unit 20 formed by collecting two or more electrically connected electric storage elements 1 is further collected. The electric storage device 30 may also include a bus bar (not shown) that electrically connects the two or more electric storage elements 1, a bus bar (not shown) that electrically connects the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) that monitors the state of one or more electric storage elements.
[0095] <Method for Manufacturing Electric Storage Element> The manufacturing method of the storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body, preparing an electrolyte, and storing the electrode body and the electrolyte in a container. Preparing the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or winding the positive electrode and the negative electrode through a separator.
[0096] The electrolyte may be stored in the container by appropriately selecting from known methods. For example, when a non-aqueous electrolyte is used as the electrolyte, the non-aqueous electrolyte may be injected from an injection port formed in the container and then the injection port may be sealed.
[0097] <Other Implementation Methods> It should be noted that the negative electrode for the storage element and the storage element of the present invention are not limited to the above-mentioned embodiments, and various changes can be made within the scope of the main purpose of the present invention. For example, the structure of another embodiment can be added to the structure of a certain embodiment, and a part of the structure of a certain embodiment can be replaced with the structure of another embodiment or a known technology. Furthermore, a part of the structure of a certain embodiment can be deleted. In addition, a known technology can be added to the structure of a certain embodiment.
[0098] In the above embodiment, the case where the storage element is used as a non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) capable of charge and discharge is described, but the type, shape, size, capacity, etc. of the storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors or lithium ion capacitors. In addition, the storage element of the present invention can also be applied to a storage element whose electrolyte is an electrolyte other than a non-aqueous electrolyte, that is, a storage element whose electrolyte contains water, etc.
[0099] In the above embodiment, the electrode body is described as a positive electrode and a negative electrode stacked with a separator interposed therebetween, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state where a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. Example
[0100] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.
[0101] [Example 1] (Production of negative electrode) A negative electrode mixture paste is prepared by mixing graphite as a negative electrode active material, carboxymethyl cellulose (CMC-A) as a cellulose derivative, styrene-butadiene rubber (SBR-A) as binder particles (particle-shaped binder), and water as a dispersion medium. It should be noted that the mass ratio of graphite, CMC-A and SBR-A is set to 98:1:1 (solid content conversion). The negative electrode mixture paste is applied to both sides of a copper foil as a negative electrode substrate and dried. Then, roll pressing is performed to obtain the negative electrode of Example 1. The peak molecular weight of the cellulose derivative (CMC-A) in the negative electrode active material layer of the obtained negative electrode is 2,520,000. The average circularity of the binder particles (SBR-A) is 0.93, and the average particle size is 210nm. In addition, the density of the negative electrode active material layer is 1.3g / cm 3 .
[0102] (Production of positive electrode) LiNi is used as the positive electrode active material 3 / 5 Co 1 / 5 Mn 1 / 5 The positive electrode mixture paste is prepared by using O2, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. It should be noted that the mass ratio of the positive electrode active material, AB, and PVDF is set to 93:4:3 (solid content conversion). The positive electrode mixture paste is applied to both sides of the aluminum foil as the positive electrode substrate and dried. Then, roll pressing is performed to obtain a positive electrode.
[0103] (Preparation of non-aqueous electrolyte) In a solvent prepared by mixing ethylene carbonate and ethyl methyl carbonate at a volume ratio of 30:70, 1.0 mol / dm 3 LiPF6 was dissolved in a concentration of to prepare a non-aqueous electrolyte.
[0104] (Production of energy storage elements) An electrode body was prepared using the negative electrode, the positive electrode, and a separator, and housed in a container together with the nonaqueous electrolyte to obtain an electric storage element of Example 1. A polyolefin microporous film was used as the separator.
[0105] [Examples 2, 3 and Comparative Examples 1 to 4] Negative electrodes and energy storage devices of Examples 2 and 3 and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1 except that the cellulose derivative and binder particles used in the preparation of the negative electrode were those described in Table 1.
[0106] CMC-B in Table 1 is CMC with a peak molecular weight of 3,180,000. CMC-C is CMC with a peak molecular weight of 280,000. SBR-B is SBR particles with an average circularity of 0.90 and an average particle size of 180 nm. SBR-C is SBR particles with an average circularity of 0.86 and an average particle size of 210 nm.
[0107] (Initial charge and discharge) For each of the obtained storage elements, constant current charging was performed at 25°C with a charging current of 1.0C and a charging end voltage of 4.20V, and then constant voltage charging was performed at 4.20V. The end condition of charging was set until the total charging time reached 3 hours. Then, a rest time of 10 minutes was set. Then, constant current discharge was performed with a discharge current of 1.0C and a discharge end voltage of 2.75V. Thus, 100% of the measured discharge capacity was set as SOC100%, and 50% of the measured discharge capacity was set as SOC50%.
[0108] (Evaluation: Resistance) Each of the obtained storage elements was charged at a constant current of 1.0C at 25°C to a SOC of 50%. After being stored in a thermostatic chamber at -10°C for 4 hours, the elements were discharged at a current of 0.1C, 0.2C or 0.3C for 30 seconds respectively. After each discharge was completed, constant current charging was performed at a current of 1.0C to a SOC of 50%. The relationship between the current in each discharge and the voltage at the tenth second after the start of the discharge was plotted, and the resistance was determined from the slope of the straight line obtained by plotting the three points. For each resistance obtained, a comparison was made between storage elements using the same cellulose derivative, and the relative values are shown in Table 1 with the resistance of the storage element whose binder particles are SBR-B as the reference (100%). That is, Examples 1, 2 and Comparative Example 1 are relative values based on Example 2. Comparative Examples 2 to 4 are relative values based on Comparative Example 3. It should be noted that with respect to Example 3, there are no other examples and comparative examples for comparison.
[0109] (Evaluation: Coulomb efficiency) Next, for each storage element, in a constant temperature chamber at 25°C, constant current charging was performed at a current of 3.0C to a voltage equivalent to SOC100%, and then constant current discharge was performed at a current of 3.0C to a voltage equivalent to SOC0%. A rest time of 10 minutes was set after charging and discharging, respectively. The above-mentioned charging and discharging cycles were performed for 10 cycles. The percentage of the discharge capacity of the tenth cycle in the charge and discharge cycle test relative to the charge capacity of the tenth cycle was calculated as the coulomb efficiency. The obtained coulomb efficiency is shown in Table 1.
[0110] [Table 1]
[0111] As shown in Table 1, the coulombic efficiency of each of the energy storage elements of Examples 1 to 3 and Comparative Example 1 using a cellulose derivative having a peak top molecular weight of 2,800,000 or less was 100.0%. In addition, from the comparison between Examples 1 and 2 and Comparative Example 1, it can be confirmed that the resistance of the energy storage element decreases as the average circularity of the binder particles increases. From such results, it can be seen that the negative electrode having a peak top molecular weight of a cellulose derivative of 2,800,000 or less and an average circularity of the binder particles of 0.90 or more can improve the coulombic efficiency of the energy storage element and reduce the resistance. In addition, when each storage element was disassembled after the above-mentioned coulombic efficiency evaluation, in each storage element of Comparative Examples 2 to 4 with low coulombic efficiency, metal lithium was visually confirmed to be precipitated on the surface of the negative electrode. On the other hand, in each storage element of Examples 1 to 3 with high coulombic efficiency, metal lithium was not confirmed to be precipitated on the surface of the negative electrode. From such results, it can be judged that each storage element of Examples 1 to 3 with high coulombic efficiency also has excellent charge acceptance.
[0112] It should be noted that, for each cellulose derivative used, the weight average molecular weight was measured together with the peak top molecular weight by the above-mentioned GPC measurement, and the weight average molecular weight of CMC-A was greater than the weight average molecular weight of CMC-B. It is believed that the correlation between the peak top molecular weight and the weight average molecular weight of the cellulose derivative is low, and the effect of the present invention leads to a small peak top molecular weight of the cellulose derivative.
[0113] (Evaluation: Charge and discharge cycle performance) Next, in order to investigate the effect of the peak molecular weight on the charge and discharge cycle performance, for each storage element of the above-mentioned Example 2, Comparative Example 3 and Example 3 using adhesive particles with the same average circularity, a charge and discharge cycle test was carried out after the above-mentioned initial charge and discharge and resistance evaluation. In a constant temperature chamber at 45°C, constant current charging was performed at a current of 1.0C to a voltage equivalent to SOC100%, and then constant current discharge was performed at a current of 1.0C to a voltage equivalent to SOC0%. A rest time of 10 minutes was set after charging and discharging, respectively. The above-mentioned charge and discharge cycle was carried out for 300 cycles. The percentage of the discharge capacity of the 300th cycle in the charge and discharge cycle test relative to the discharge capacity of the first cycle was calculated as the capacity retention rate. The calculated capacity retention rate is shown in Table 2.
[0114] [Table 2]
[0115] As shown in Table 2, it can be seen that the use of a cellulose derivative having a peak molecular weight that is not too small is preferred in terms of charge and discharge cycle performance. It is speculated that this is because by using a cellulose derivative having a peak molecular weight that is not too small, a good negative electrode mixture paste can be prepared, and the aggregation of binder particles is also suppressed, thereby improving the uniformity of the negative electrode active material layer and the adhesion to the negative electrode substrate. Industrial availability
[0116] The present invention can be applied to a power storage element and a negative electrode thereof used as a power source for electronic devices such as personal computers and communication terminals, and automobiles. Description of Reference Numerals
[0117] 1: electricity storage element, 2: electrode body, 3: container, 4: positive electrode terminal, 41: positive electrode lead, 5: negative electrode terminal, 51: negative electrode lead, 20: electricity storage unit, 30: electricity storage device.
Claims
1. A negative electrode for an electric storage element, comprising a negative electrode active material layer containing a negative electrode active material, a cellulose derivative and binder particles, The peak top molecular weight of the cellulose derivative is 2,800,000 or less, The binder particles have an average circularity of 0.90 or more.
2. The negative electrode for an electric storage element according to claim 1, wherein The negative electrode active material is a carbon material, and the negative electrode active material layer contains 90 mass % or more of the negative electrode active material.
3. The negative electrode for an electric storage element according to claim 1, wherein The binder particles include particles of styrene butadiene rubber.
4. The negative electrode for an electric storage element according to claim 1, wherein The cellulose derivative comprises carboxymethyl cellulose. 5 . An electric storage device comprising the negative electrode for an electric storage device according to claim 1 .
Citation Information
Patent Citations
Negative electrode composite for lithium battery, and negative electrode and lithium battery using the composite
JP2005011808A